Beyond Human Scale: The Large Corporation at RiskBeyond Human Scale: The Large Corporation at Risk, by GinzbergEli and VojtaGeorge. New York: Basic Books, 1985, 242 pp., $16.95, cloth. - Stablein, Ralph (Academy of Management Review, 1986)
The article presents a review of the book “Beyond Human Scale: The Large Corporation at Risk,” by Eli Ginzberg and George Vojta.